A prospective evaluation of microvascular complications in diabetes mellitus patients at time of diagnosis - Prasad, Ramadhenu Rajendra; Sekhar, Valluri Some; Rajyalakshmi, M. (International Journal of Advances in Medicine, 2020)
Background: The microvascular complication is also showing increasing trend. This is because of lack of awareness and lack of regular screening programme. Early diagnosis and Intensive glycemic control has been the most effective approach to prevent the progress of microvascular complication. Methods: Based on exclusion and inclusion criteria 100 patients were enrolled for this study. For diagnosis of diabetes mellitus, we used American Diabetes Association (ADA) guidelines was followed. Detail history of patient was taken related to microvascular complication and they underwent extensive medical examination for the assessment of microvascular complications. Results: Mean age of patient with microangiopathy was 59.942±7.18 years and without microangiopathy was 54.31±13.15years. Microangiopathy was common in patient whose HbA1c was more than 10.7. Out of 26 patient 20 patient having microangiopathy. Neuropathy was present in 31 patients and absent in 69 patients. Conclusions: It was observed that a continuous linear association between HbA1c and microvascular complications. This is more common in patient in patient with higher HbA1c. Neuropathy is most common which is followed by nephropathy and retinopathy least among all.